Anti-angiogenesis through noninvasive to minimally invasive intraocular delivery of the peptide CC12 identified by in vivo-directed evolution. (January 2017) - Chen, Chong; Liu, Kun; Xu, Yupeng; Zhang, Pengwei; Suo, Yan; Lu, Yi; Zhang, Wenyuan; Su, Li; Gu, Qing; Wang, Huamao; Gu, Jianren; Li, Zonghai; et al.
Abstract: Anti-vascular endothelial growth factor (VEGF) therapies are widely used for the treatment of neovascular fundus diseases such as diabetic retinopathy. However, these agents need to be injected intravitreally, because their strong hydrophilicity and high molecular weight prevent them from penetrating cell membranes and complex tissue barriers. Moreover, the repeated injections that are required can cause infection and tissue injury. In this study, we used in vivo -directed evolution phage display technology to identify a novel dodecapeptide, named CC12, with the ability to penetrate the ocular barrier in a noninvasive (via conjunctival sac instillation) or minimally invasive (via retrobulbar injection) manner. KV11, an antiangiogenesis peptide previously demonstrated to inhibit pathological neovascularization in the retina, was then used as a model antiangiogenesis cargo for CC12. We found that conjugation of KV11 peptide with CC12 peptide facilitated the delivery of KV11 to the retina, resulting in significant inhibition of retinal neovascularization development via topical application without tissue toxicity. Collectively, our data of multilevel evaluations demonstrate that CC12 may enable the noninvasive to minimally invasive intraocular delivery of antiangiogenic therapeutics.